NILAI-NILAI PENDIDIKAN TAUHID PADA NOVEL “SULUK ABDUL JALIL” KARYA AGUS SUNYOTO - AL-FARISI, MOCHAMMAD ALBY; SIROJUDIN, RUMBANG; ARIFIN, MOH.NUR; LAZZAVIETAMSI, FANDY ADPEN; WASEHUDIN, WASEHUDIN (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
The worldview of tawhid is not only to worship Allah as believed by monotheists, but also recognizes the unity of creation, the unity of humanity, the unity of life guidance and the unity of life goals, all of which are derivation from the unity of divinity (Rais, 1991: 18). Education is a tool or can also be called a very useful investment this research uses a qualitative descriptive research approach. Multiple descriptions are used to identify guiding concepts and explanations that produce conclusions. Inductive in nature, explaining and revealing is the goal. While the research design is a case study, which is a procedure for collecting and reviewing information on a case. This research aims to collect data on the values of tawhid education in the new Suluk Abdul Jalil. Sheikh Datuk Abdul Jalil's philosophical stance on existence and existence itself is covered in Book One along with various spiritual experiences aimed at reaching the Absolute. The novel